Strengthening the Socioanthropology of Civil Society in the Era of Democracy Disruption - Sumarna, Andri; Haryono, Merda Budi; Fauzi, Sudar; Hanapia, Cepi; Ramdhani, Topik (Journal of English Language and Education, 2024)
Socioanthropology is a science that studies the characteristics and relationships between societies and their cultures. A nation's civilization is a reflection of the characteristics and relationships between these societies and their cultures. Culture itself serves as a nation's identity, encompassing human morals and reason. Maturity of thought and maturity in society, nation, and state are essential prerequisites for establishing relationships between societies and their characteristics. These can be described as the customs of local communities rooted in hundreds, even thousands of years. Since entering the reform era in 1998, democratic life in Indonesia has demonstrated a phenomenon rare in any other country in the world. This maturity of thought and maturity in society, nation, and state is also referred to as democratic life. Democracy will thrive if the characteristics and relationships between societies and their cultures are well-established; this combination of human morals and reason is called civil society. Indonesia has adopted multi-party democracy for the second time since its independence on August 17, 1945, with the establishment of 12 multi-party political parties. Since the reform era in May 1998, Indonesia has returned to liberal democracy with a multi-party system consisting of dozens of political parties. This contrasts with the US and the UK, the birthplaces of liberal democracy, which only have two political parties.